From smart city to artificial intelligence city. Envisaging the future of urban planning - Romano Fistola; Rosa Anna La Rocca (TeMA: Journal of Land Use, Mobility and Environment)
The paper emphasizes the need to advance both theoretical and methodological understandings to reflect the theoretical-methodological evolution of urban planning, considering the vast potential of Artificial Intelligence (AI). Specifically, the paper aims to chart an innovative path for the discipline of urban planning by adopting a systemic approach to studying urban phenomena and envisioning how the intentional integration of AI can lead to a completely new way of managing urban transformation. The study seeks to provide a fresh perspective on AI's potential impact, especially within fields overseeing urban and territorial changes. It begins with an analysis of the relationship between technological innovation and urban transformation, which is crucial today due to the opportunities AI presents. The paper particularly focuses on the relationships among urban sub-systems, which are essential for city survival. Historically, from the inception of urban planning to the rise of smart cities, the integration of technology and urban environments often lacked a cohesive theoretical framework to guide the deliberate adoption of technological innovations. The primary aim of the paper is to highlight the urgent need to build a theoretical and disciplinary foundation that recognizes AI's creative capacity and effectively utilizes its capabilities to design sustainable future urban configurations in harmony with existing resources.